The theophany report of Psalm 18 as an expression of an alternative reality - Mare, L. P. (Journal for Semitics, 2010)
Poetical texts have an inherent imaginative quality where a world of new possibilities within the covenantal relationship is generated. Such poetry describes not only a world that is known to be true, but it also summons and evokes such a world. Thus, the poets of ancient Israel, by use of the imagination, spoke the possibilities of new realities into being in times of crisis. The purpose of this article is to investigate how a poetical text that describes the appearance of Yahweh on behalf of his people expresses these alternative realities. The theophany report occurs frequently in the Old Testament. The focus in these reports is not the mercy or care of God; instead Yahweh is envisioned as a warrior God who fights on behalf of his covenant partner. For the purpose of this study Psalm 18 will be analyzed with a specific focus on the theophany report in verses 8-16 to ascertain what the function of this report is and how it expresses an alternative reality to the readers/hearers of the text.
paid